Impact of Background Fruit Odors on Attraction of Drosophila suzukii (Diptera: Drosophilidae) to Its Symbiotic Yeast. Issue 2 (10th March 2021) - Huang, Juan; Gut, Larry J
Abstract: Background odors produced by plants in the environment can interfere with the response of insects to a point-releasing attractant, especially when their compositions overlap. In this study, a series of binary choice tests was conducted in a wind tunnel to investigate whether background odors emitted from cherry, blueberry, blackberry, or raspberry fruits would affect the level of Drosophila suzukii (Matsumura) attraction to its symbiotic yeast, Hanseniaspora uvarum (Niehaus) (Saccharomycetales: Saccharomycetaceae). Whether an increase in the intensity of background odors would affect the attractiveness of H. uvarum to D. suzukii was also investigated, either by increasing the number of cherry or raspberry fruit per cup or by increasing the number of fruit cups surrounding the cup baited with the yeast. In wind tunnel assays, background fruit odors interfering with D. suzukii attraction to the yeast varied among fruit types. Raspberry odor inhibited the attractiveness of H. uvarum to the fly the most, followed by blackberry odor, whereas cherry and blueberry odors had no significant impact on the attraction. An increase in the intensity of odors by adding more cherry or raspberry fruit per cup did not increase the impact of fruit odor on the attraction; however, adding more raspberry cups around H. uvarum linearly decreased its attractiveness, suggesting that background host fruit abundance and likely increase in host odor may influence D. suzukii attraction to yeast odor depending on host species.